Integrating competency based-management into individual development plan for university staff / Mohamad Nasaruddin Mahdzir ...[et al.] - Mahdzir, Mohamad Nasaruddin; Abd Rahim, Ahmad Shahril Azwan; Mohd Seni, Mohammad Khair; Othman, Abdul Kadir (Universiti Teknologi MARA, 2021)
The purpose of this study is to examine the Individual Development Plan (IDP) of university administrators especially those who are categorised under the professional and management scheme. The IDP explains the dimensions of Attitude, Skills and Knowledge required by the administrators in order to perform their responsibilities in executing the management functions and be as the backbone of the university to achieve its mission, vision and objectives of institution. In general, IDP is expected to enhance the performance and abilities of an individual. Thus, the assimilation of IDP into talent management will enable the Human Resource Department to plan the structured Talent Development Programmes that in line with the University Strategic Planning and Key Performance Indicators of University.